Shear tests of GFRP-reinforced concrete beams strengthened in shear by textile reinforced concrete. (December 2021) - Tran, Cao Thanh Ngoc; Nguyen, Xuan Huy; Le, Anh Tuan; Nguyen, Huy Cuong; Le, Dang Dung
Abstract: Shear tests on six GFRP reinforced concrete beams with aspect ratios ranging from 2.3 to 2.8 are conducted in this research to investigate the effectiveness of using textile reinforced concrete in shear strengthening. The beams are strengthened with either one or two layers of U-wrapping textile reinforced concrete. Two levels of aspect ratios of 2.3 and 2.8 are studied in this experimental program. The load–displacement curves, cracking patterns, strains in FRP bars are recorded and compared between strengthened and un-strengthened GFRP-reinforced concrete beams. Textile reinforced concrete has proved its capability in enhancing the shear strengths of tested beams with various aspect ratios. Increasing the number of fibres layers in textile reinforced concrete has shown its effectiveness in increasing both shear strengths and post-elastic stiffnesses of the beams. The diagonal tension failure together with rupture or slippage of fibres in textile reinforced concrete are observed at the level of maximum shear forces. A simple analytical model is proposed to predict the shear strengths of the tested beams.